Anti-Drug Policies in Colombia : Successes, Failures, and Wrong Turns - Gaviria, Alejandro, 1966-; Mejia, Daniel (Book collections on Project MUSE., 2015)
"This book compiles the most up-to-date research and evidence on the different dimensions of drugs and drugs policy in Colombia, a country that has done everything possible to fight illicit drug production and trafficking"--